On the determinants of changes in wage inequality in Bolivia - Gustavo Canavire-Bacarreza; Fernando Rios-Avila (Levy Economics Institute of Bard College, 2015)
In recent years, Bolivia has experienced a series of economic and political transformations that have directly affected the labor markets, particularly the salaried urban sector. Real wages have shown strong increases across the distribution, while also presenting a decrease in inequality. Using an intertemporal decomposition approach, we find evidence that changes in demographic and labor market characteristics can explain only a small portion of the observed inequality decline. Instead, the results indicate that the decline in wage inequality was driven by the faster wage growth of usually low-paid jobs, and wage stagnation of jobs that require higher education or are in traditionally highly paid fields. While the evidence shows that the reduction in inequality is significant, we suggest that such an improvement might not be sustainable in the long run, since structural factors associated with productivity, such as workers' level of education, explain only a small portion of these wage changes.
Keywords: D63; I31; J31; 330; Bolivia; Decomposition; Wage Inequality